Risk Factors Causing Repeat Breeding Reproductive Disorders in Beef Cattle in Klabang Sub-District, Bondowoso Regency - Rofiqi, Mohammad Miftahur; Saputro, Amung Logam; Praja, Ratih Novita (Journal of Basic Medical Veterinary, 2023)
This study aims to determine the relationship between factors and cases of repeated breeding in beef cattle in Klabang District, Bondowoso Regency. Beef cattle farming in Klabang District, Bondowoso Regency is currently experiencing problems in meeting the demand for beef due to low productivity. These problems occur due to cases of repeated breeding and decreased livestock efficiency and productivity. This case is suspected due to the lack of sanitation from farmers. This descriptive study used 69 cows with a simple random sampling method. Primary data was obtained from direct observation of livestock, followed by interviews with farmers using an in-depth study system. Meanwhile, secondary data was obtained from inseminator records which included the period of cultivation, the farmer's ability to detect the estrous cycle, and the farmer's knowledge of reproduction, housing, feeding, and copulation in beef cattle. The collected data were analyzed using descriptive statistics and then processed using SPSS 22.0. The Chi-Square test (X2) is used to determine the relationship between causative factors and repeated breeding. The results of this study indicate that the incidence of repeated breeding in Klabang District, Bondowoso Regency is 100% of the sample. All factors such as length of breeding, farmer's ability to detect estrous cycles, and farmer's knowledge about reproduction, housing, feed, age of livestock, and copulation in beef cattle correlate with the incidence of repeated breeding.